Change in steam generators main and auxiliary energy flow streams during the load increase of LNG carrier steam propulsion system - Mrzljak, Vedran (Array, 2018)
In this paper is presented an analysis of main and auxiliary steam energy flow streams from steam generators during the increase in steam system load at conventional LNG carrier. During the steam system load increase was presented differences in steam pressure and temperature between main and auxiliary steam flow streams. Energy power of the auxiliary flow stream is higher than energy power of the main flow stream only at the lowest steam system loads after which main flow stream takes over primacy at middle and high steam system loads. Cumulative auxiliary energy flow stream was divided on energy flow streams to each auxiliary device and energy power consumption of each auxiliary device was also investigated throughout number steam system loads. Analysis of steam production from marine steam generators presented in this paper provides insight into the operation dynamics of the entire steam propulsion system.